The influence of bone graft procedures on primary stability and bone change of implants placed in fresh extraction sockets - Sang Ho Jun; Chang-Joo Park; Suk-Hyun Hwang; Youn Ki Lee; Cong Zhou; Hyon-Seok Jang; Jae-Jun Ryu (SpringerOpen, 2018)
Abstract Background This study was to evaluate the effect of bone graft procedure on the primary stability of implants installed in fresh sockets and assess the vertical alteration of peri-implant bone radiographically. Methods Twenty-three implants were inserted in 18 patients immediately after tooth extraction. The horizontal gap between the implant and bony walls of the extraction socket was grafted with xenografts. The implant stability before and after graft procedure was measured by Osstell Mentor as implant stability quotient before bone graft (ISQ bbg) and implant stability quotient after bone graft (ISQ abg). Peri-apical radiographs were taken to measure peri-implant bone change immediately after implant surgery and 12 months after implant placement. Data were analyzed by independent t test; the relationships between stability parameters (insertion torque value (ITV), ISQ abg, and ISQ bbg) and peri-implant bone changes were analyzed according to Pearson correlation coefficients. Results The increase of ISQ in low primary stability group (LPSG) was 6.87 ± 3.62, which was significantly higher than the increase in high primary stability group (HPSG). A significant correlation between ITV and ISQ bbg (R = 0.606, P = 0.002) was found; however, age and peri-implant bone change were not found significantly related to implant stability parameters. It was presented that there were no significant peri-implant bone changes at 1 year after bone graft surgery. Conclusions Bone graft procedure is beneficial for increasing the primary stability of immediately placed implants, especially when the ISQ of implants is below 65 and that bone grafts have some effects on peri-implant bone maintenance.